Police Amalgamation and Reform in Scotland: The Long Twentieth Century. (April 2016) - Davidson, Neil; Jackson, Louise A.; Smale, David M.
Abstract : This article examines shifting debates about police amalgamation and governance reform in Scotland since the mid-nineteenth century in the light of the creation of a single police service (Police Scotland) in 2013. From a proliferation of 89 separate police forces in 1859, the number had been reduced to 48 by 1949 and eight in 1975. Yet the move towards a single police service was far from inevitable, as comparison with England and Wales demonstrates. The idea of a 'single' or national force was mooted from the 1850s onwards in moments of unrest, disorder and emergency, but for most of the twentieth century it remained anathema. For the Scottish Office and Home Office as well as for many police officers, the move towards larger policing units was seen as desirable on the grounds of economy, efficiency, and professionalisation. Yet the assumption that 'local' control of police forces through municipal and county councils best enabled accountability and hence legitimacy remained intact until the 1960s, whilst the regional model set up in 1975 persisted for forty years. The article explores the reasons for this, focusing on the changing dynamics of the relationship between central and local government across the last 150 years.